Feasibility of a Low-Intensity, Technology-Based Intervention for Increasing Physical Activity in Adults at Risk for a Diabetic Foot Ulcer: A Mixed-Methods Study. (September 2019) - Schneider, Kristin L.; Crews, Ryan T.; Subramanian, Vasanth; Moxley, Elizabeth; Hwang, Sungsoon; DiLiberto, Frank E.; Aylward, Laura; Bean, Jermaine; Yalla, Sai
Background: Among adults with diabetes, 19-34% will develop a diabetic foot ulcer (DFU), which increases amputation risk and health care costs, and worsens quality of life. Regular physical activity, when increased gradually, may help prevent DFUs. In this mixed-methods study, we examined the feasibility of a low-intensity, technology-based behavioral intervention to increase activity in adults at risk for DFUs. Method: Participants at risk for a DFU (n = 12; 66% female; mean age = 59.9 years) received four in-person exercise and behavioral counseling sessions over 2-3 weeks, supplemented with use of an activity monitor (to track steps) and text messages (to reinforce behavioral strategies) for an added 8 weeks. Pre- and postintervention assessments of accelerometer measured activity, daily mobility, and glycemic control (A1C) were completed. Treatment acceptability was assessed by questionnaire and via key informant interview. Results: The program appears feasible since all but one participant attended all four sessions, all used the activity monitor and all responded to text messages. Treatment acceptability (scale: 1 = very dissatisfied, 5 = extremely satisfied) was high; average item ratings were 4.79 (SD = 0.24). Participants increased their steps by an average of 881.89 steps/day ( d = 0.66). A1C decreased on average by 0.33% ( d = 0.23). Daily mobility did not change. Interview results suggest that participants perceived benefits from the intervention. Participant recommended improvements included providing more physical activity information, addressing pain, and intervention delivery in a podiatry clinic. Conclusion: Individuals at risk for a DFU might benefit from a minimally intensive, technology-based intervention to increase their physical activity. Future research comparing the intervention to usual care is warranted.